Factors affecting dairy milk production and their associations under practical conditions in Northeastern Thailand - Supakorn, C.; Deawtrakoon, P.; Maneerat, W. (Journal of the Indonesian Tropical Animal Agriculture, 2026)
This study investigated factors influencing milk production in terms of quantity (raw milk yield) and quality (%fat, %protein, %lactose, %total solids, and log somatic cell counts (log SCC)) and exam-ined the associations among these traits in the morning (am) and evening (pm) milking sessions. Data were collected from the Herd Health Unit under the supervision of the Livestock Regional Office 3, Northeastern Thailand, during 2022 to 2025. Statistical analyses included analysis of variance (ANOVA) to assess fixed effects, Tukey’s Honestly Significant Difference (HSD) test for mean com-parisons, and Pearson’s correlation analysis. Fixed effects included diurnal difference, groups of tem-perature-humidity index (THI), milk collecting center types (MCC type), and their interactions. The interaction between diurnal difference and MCC type significantly affected raw milk yield, %fat, %lactose, %total solids, and log SCC (P < 0.001). Morning milk yield was highest in dairy cooperatives (10.80 tons; P < 0.05), while evening fat percentages were highest in private organizations (4.02%) and dairy cooperatives (3.97%) (P < 0.05). Lactose percentages were significantly lower in the university affiliated centers for both morning (4.55%) and evening (4.56%) sessions (P < 0.05). Morning total solids were highest in private organizations (12.8%) and dairy cooperatives (12.6%) (P < 0.05), and log SCC values were generally higher in the morning across all MCC types. The THI significantly influ-enced %lactose and %total solids (P < 0.001), with THI class A (72 to79.9) exhibiting higher lactose (4.7%) and total solids (12.6%) than other classes (P < 0.05). Correlation analyses demonstrated signif-icantly positive associations between the traits in the morning and evening sessions (r = 0.52 to 0.79), positive correlations between raw milk yield and milk composition across diurnal differences (r = -0.05 to 0.83), negative correlations between milk composition and log SCC (r = -0.38 to -0.01), and low positive correlations between raw milk yield and log SCC (r = 0.08 to 0.11). These findings demon-strate that milking time, MCC type, and heat stress all contribute to the composition and yield of milk, providing insights for the optimization of dairy management in tropical conditions.